DIALEKTIKA KOMUNIKASI INTRAPERSONAL: MENGKAJI PESONA KOMUNIKASI DENGAN DIRI SENDIRI - Ferry Adhi Dharma (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
The dialectic of intrapersonal communication help us to understand several sides of metaphysics in the science of communication. At this level of communication, communication activities can be analyzed from the dialectic and the dialogue which is in monologue concept. Objectivity of communicative action will be traced from intersubjectivity of each individual. In this article, the communicative action will be reviewed by a phenomenal figure of Dimas Kanjeng Taat Pribadi. By reviewing and studying at this level of communication, we will try to understand the construction of knowledge, attitudes, and the subjective actions of individuals that necessitate a distinctive or enchanting communication style when they communicate with others.